Aplikasi android inventaris perlengkapan untuk membantu kegiatan karang taruna RW 01 sokaraja kidul - Jatmiko Indriyanto; Purwono; Iis setiawan Mangku Negara (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
Equipment inventory management for Karang Taruna (Youth Organization) activities in RW 01 Sokaraja Kidul has been done manually, often leading to problems such as disorganized data, difficulty in retrieval of information, and the potential for data loss or inconsistencies. This research aims to design and develop an Android-based application that can facilitate more effective and efficient data collection, management, and inventory monitoring.The methods used in this research include data collection through observation and interviews, followed by system design using a software development model approach. The developed application has key features such as item recording, inventory grouping, loan and return recording, and digital report presentation.The results of this study indicate that the Android-based inventory application can improve data management, accelerate information retrieval, and minimize recording errors. With this system, it is hoped that the administrative activities of Karang Taruna (Youth Organization) in RW 01 Sokaraja Kidul will be more orderly, transparent, and structured.